p16(INK4a) suppression by glucose restriction contributes to human cellular lifespan extension through SIRT1-mediated epigenetic and genetic mechanisms. - Yuanyuan Li; Trygve O Tollefsbol (PLoS ONE, 2011)
Although caloric restriction (CR) has been shown to increase lifespan in various animal models, the mechanisms underlying this phenomenon have not yet been revealed. We developed an in vitro system to mimic CR by reducing glucose concentration in cell growth medium which excludes metabolic factors and allows assessment of the effects of CR at the cellular and molecular level. We monitored cellular proliferation of normal WI-38, IMR-90 and MRC-5 human lung fibroblasts and found that glucose restriction (GR) can inhibit cellular senescence and significantly extend cellular lifespan compared with cells receiving normal glucose (NG) in the culture medium. Moreover, GR decreased expression of p16(INK4a) (p16), a well-known senescence-related gene, in all of the tested cell lines. Over-expressed p16 resulted in early replicative senescence in glucose-restricted cells suggesting a crucial role of p16 regulation in GR-induced cellular lifespan extension. The decreased expression of p16 was partly due to GR-induced chromatin remodeling through effects on histone acetylation and methylation of the p16 promoter. GR resulted in an increased expression of SIRT1, a NAD-dependent histone deacetylase, which has positive correlation with CR-induced longevity. The elevated SIRT1 was accompanied by enhanced activation of the Akt/p70S6K1 signaling pathway in response to GR. Furthermore, knockdown of SIRT1 abolished GR-induced p16 repression as well as Akt/p70S6K1 activation implying that SIRT1 may affect p16 repression through direct deacetylation effects and indirect regulation of Akt/p70S6K1 signaling. Collectively, these results provide new insights into interactions between epigenetic and genetic mechanisms on CR-induced longevity that may contribute to anti-aging approaches and also provide a general molecular model for studying CR in vitro in mammalian systems.